2020
DOI: 10.1111/1751-7915.13553
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic modulation of redox state confounds fish survival against Vibrio alginolyticus infection

Abstract: Vibrio alginolyticus threatens both humans and marine animals, but hosts respond to V. alginolyticus infection is not fully understood. Here, functional metabolomics was adopted to investigate the metabolic differences between the dying and surviving zebrafish upon V. alginolyticus infection. Tryptophan was identified as the most crucial metabolite, whose abundance was decreased in the dying group but increased in the survival group as compared to control group without infection. Concurrently, the dying zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Recent reports have indicated that bacterial sensitivity to antibiotics and host ability against bacteria are bacterial metabolic state‐ and host metabolic state‐dependent respectively (Zeng et al ., 2017; Cheng et al ., 2018; Yang et al ., 2018; Cheng et al ., 2019; Xu et al ., 2019; Jiang et al ., 2019b; Gong et al ., 2020). The present study explored the relationship between gentamicin resistance and ROS in V .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that bacterial sensitivity to antibiotics and host ability against bacteria are bacterial metabolic state‐ and host metabolic state‐dependent respectively (Zeng et al ., 2017; Cheng et al ., 2018; Yang et al ., 2018; Cheng et al ., 2019; Xu et al ., 2019; Jiang et al ., 2019b; Gong et al ., 2020). The present study explored the relationship between gentamicin resistance and ROS in V .…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the metabolomes of dying fish and survival fish, we and other groups have shown that supplementation of zebrafish or tilapia with glucose, stearic acid, proline, serine, L-aspartic acid, or L-leucine could regulate the expression of immune-related genes and eventually increase fish's survival upon the infection by Vibrio alginolyticus, Streptococcus iniae, Streptococcus agalactiae, or Edwardsiella tarda (Peng et al, 2015b;Du et al, 2017;Cheng et al, 2019). It was also revealed that tryptophan increased zebrafish survival to V. alginolyticus infection by downregulating the production of ROS to avoid excessive immune response (Gong Q. Y. et al, 2020). In addition, metabolism-based approach also found that maltose, palmitic acid, threonine, and taurine enhanced zebrafish survival to Aeromonas sorbrial or E. tarda infection at higher temperature (Jiang et al, 2019a).…”
Section: Introductionmentioning
confidence: 93%
“…Thus, a synergistic use of antibiotics with ROS generation promoter or/and ROS degradation inhibitor will elevate the antibiotic-mediated killing. In addition, metabolites promoting hosts to eliminate bacterial pathogens have been reported ( Jiang et al, 2019a , b , 2020b ; Gong et al, 2020a , b ; Yang et al, 2020 ), where ROS are involved ( Sarr et al, 2018 ; Gong et al, 2020b ). Thus, it is possible to select the promoters or/and inhibitors that simultaneously elevate the ROS level of both hosts and bacteria.…”
Section: Discussionmentioning
confidence: 99%